Capacity Enhancement of Hepatitis C Virus Treatment through Integrated, Community-Based Care - Warren D Hill; Gail Butt; Maria Alvarez; Mel Krajden (Canadian Journal of Gastroenterology)
BACKGROUND: An estimated 250,000 Canadians are infected with the hepatitis C virus (HCV). The present study describes a cohort of individuals with HCV referred to community-based, integrated prevention and care projects developed in British Columbia. Treatment outcomes are reported for a subset of individuals undergoing antiviral therapy at four project sites.